Potential of Sharia Financial Institutions in Supporting Indonesia's Economic Growth - Fahmi, Annas Syams Rizal (AL-IKTISAB: Journal of Islamic Economic Law, 2019)
Basically, Islamic financial institutions have existed since the time of the Prophet SAW, but their development and inauguration have been initiated today. The existence of this institution is intended to restore the community's economic system to what has been regulated by religion with all its orders and prohibitions. The type of development is increasingly becoming an alternative to every conventional economic transaction. Islamic financial institutions in the community's view are positive enough to avoid conventional economic systems, but there are also those who think negatively due to cases experienced by a number of Islamic financial institutions. The potential possessed by Islamic finance institutions is quite large both from macro and micro economies, especially for national development through poverty reduction and gap reduction.